If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 7)(3x + 5) = 0 Reorder the terms: (7 + X)(3x + 5) = 0 Reorder the terms: (7 + X)(5 + 3x) = 0 Multiply (7 + X) * (5 + 3x) (7(5 + 3x) + X(5 + 3x)) = 0 ((5 * 7 + 3x * 7) + X(5 + 3x)) = 0 ((35 + 21x) + X(5 + 3x)) = 0 (35 + 21x + (5 * X + 3x * X)) = 0 (35 + 21x + (5X + 3xX)) = 0 Reorder the terms: (35 + 5X + 21x + 3xX) = 0 (35 + 5X + 21x + 3xX) = 0 Solving 35 + 5X + 21x + 3xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + 5X + 21x + -35 + 3xX = 0 + -35 Reorder the terms: 35 + -35 + 5X + 21x + 3xX = 0 + -35 Combine like terms: 35 + -35 = 0 0 + 5X + 21x + 3xX = 0 + -35 5X + 21x + 3xX = 0 + -35 Combine like terms: 0 + -35 = -35 5X + 21x + 3xX = -35 Add '-21x' to each side of the equation. 5X + 21x + -21x + 3xX = -35 + -21x Combine like terms: 21x + -21x = 0 5X + 0 + 3xX = -35 + -21x 5X + 3xX = -35 + -21x Reorder the terms: 35 + 5X + 21x + 3xX = -35 + -21x + 35 + 21x Reorder the terms: 35 + 5X + 21x + 3xX = -35 + 35 + -21x + 21x Combine like terms: -35 + 35 = 0 35 + 5X + 21x + 3xX = 0 + -21x + 21x 35 + 5X + 21x + 3xX = -21x + 21x Combine like terms: -21x + 21x = 0 35 + 5X + 21x + 3xX = 0 The solution to this equation could not be determined.
| 3(4x-3.2)=5x-9.6 | | 3(2-3x)=52 | | 2x-4+3x=7x-3 | | 70x+90=90 | | 7x-5=5x-6 | | x^2-6x=22 | | 6u-9+3(2u+3)=4(u+3) | | 4(x+1.78)=3x | | 8n+16=8 | | 200x-0.08=600x+0.52 | | 3x+7=-2x+27 | | 6-6x=6x-10x+10 | | 3.9x-73=2.4x+5 | | 8z-24=6+2z | | 5m-7=10+3m | | 6.2=8x+1.4 | | 6-6x=6x-10+10 | | 6n-2=1 | | -4(v-4)=-7+37 | | 2y-8+14=-6 | | 2t-7=-16+t | | 3+3u=6 | | -19=5(u-5)-8u | | -3x^3+3x^2-21x+7=0 | | p-24=-19 | | 4+x-6=6x+3x+2 | | 4x-13.2=x | | 2.4x-8.6=10.6 | | -5+2u=-13 | | 17+7=31 | | 3p+7p+22=2 | | a+bxc=21 |